Diagnosis and Therapy of Female Urinary Incontinence. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Registry No. 015/091, January 2022) - Naumann, Gert; Aigmüller, Thomas; Bader, Werner; Bauer, Ricarda; Beilecke, Kathrin; Betschart Meier, Cornelia; Bruer, Gunther; Bschleipfer, Thomas; Deniz, Miriam; Fink, Thomas; Gabriel, Boris; Gräble, Roswitha; Grothoff, Matthias; Haverkamp, Axel; Hampel, Christian; Henscher, Ulla; Hübner, Markus; Huemer, Hansjoerg; Kociszewski, Jacek; Kölbl, Heinz; Kölle, Dieter; Kropshofer, Stephan; Kuhn, Annette; Nothacker, Monika; Oelke, Matthias; Peschers, Ursula; Preyer, Oliver; Schultz-Lampel, Daniela; Tamussino, Karl; Reina Tholen†; Tunn, Ralf; Viereck, Volker; Reisenauer, Christl (Geburtshilfe und Frauenheilkunde, 2023)
Aim This completely revised interdisciplinary S2k-guideline on the diagnosis, therapy, and follow-up care of female patients with urinary incontinence (AWMF registry number: 015-091) was published in December 2021. This guideline combines and summarizes earlier guidelines such as “Female stress urinary incontinence,” “Female urge incontinence” and “Use of Ultrasonography in Urogynecological Diagnostics” for the first time. The guideline was coordinated by the German Society for Gynecology and Obstetrics (Deutsche Gesellschaft für Gynäkologie und Geburtshilfe, DGGG) and the Working Group for Urogynecology and Plastic Pelvic Floor Reconstruction (Arbeitsgemeinschaft für Urogynäkologie und plastische Beckenbodenrekonstruktion e. V., AGUB).Methods This S2k-guideline was developed using a structured consensus process involving representative members from different medical specialties and was commissioned by the Guidelines Commission of the DGGG, OEGGG and SGGG. The guideline is based on the current version of the guideline “Urinary Incontinence in Adults” published by the European Association of Urology (EAU). Country-specific items associated with the respective healthcare systems in Germany, Austria and Switzerland were also incorporated.Recommendations The short version of this guideline consists of recommendations and statements on the surgical treatment of female patients with stress urinary incontinence and urge incontinence. Specific solutions for the diagnostic workup and treatment of uncomplicated and complicated urinary incontinence are discussed. The diagnostics and surgical treatment of iatrogenic urogenital fistula are presented.
Keywords: guideline; urinary incontinence; stress urinary incontinence; urge urinary incontinence; surgical therapy; suburethral sling; colposuspension; urogenital fistula